2018
DOI: 10.1021/acs.est.8b00035
|View full text |Cite
|
Sign up to set email alerts
|

Access to Household Water Quality Information Leads to Safer Water: A Cluster Randomized Controlled Trial in india

Abstract: Household-specific feedback on the microbiological safety of drinking water may result in changes to water management practices that reduce exposure risks. We conducted a randomized, controlled trial in India to determine if information on household drinking water quality could change behavior and improve microbiological quality as indicated by Escherichia coli counts. We randomly assigned 589 participating households to one of three arms: (1) a messaging-only arm receiving messaging on safe water management (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 53 publications
0
30
0
Order By: Relevance
“…Because tests are performed by users on water they actually drink and yield a tangible colour‐change signal, such tests have the potential to convey drinking water risk information to users more convincingly than outsiders giving the same information verbally (Trent et al . ).…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Because tests are performed by users on water they actually drink and yield a tangible colour‐change signal, such tests have the potential to convey drinking water risk information to users more convincingly than outsiders giving the same information verbally (Trent et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…Work continues on developing more user‐friendly reporting platforms (Trent et al . ). Second, participant feedback from community follow‐up meetings strongly suggested that self‐testing and the resultant water quality information had a direct and immediate impact on consumers’ perception of water supplies.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations